Connections to fixed points and Sil’nikov saddle-focus homoclinic orbits in singularly perturbed systems - Battelli, F.; Palmer, K.J. (Український математичний журнал, 2008)
We consider a singularly perturbed system depending on two parameters with two (possibly the same) normally hyperbolic centre manifolds. We assume that the unperturbed system has an orbit connecting a hyperbolic fixed point on one centre manifold to a hyperbolic fixed point on the other. Then we prove some old and new results concerning the persistence of these connecting orbits and apply the results to find examples of systems in dimensions greater than three which possess Sil’nikov saddle-focus homoclinic orbits. Розглянуто сингулярно збурену систему, що залежить вiд двох параметрiв та має два (можливо, однаковi) нормально гiперболiчнi центрованi многовиди. При цьому припускається, що незбурена система має орбiту, яка поєднує гiперболiчну нерухому точку на одному центрованому многовидi з гiперболiчною нерухомою точкою на iншому. Доведено деякi вiдомi та новi результати щодо збереження цих орбiт та наведено приклади систем розмiрностi бiльше, нiж три, що мають сiдловi фокуснi гомоклiнiчнi орбiти Сiльнiкова.